Meningkatkan Kemampuan Membaca Pemahaman melalui Penerapan Metode Reciprocal Teaching Masa Covid-19 Siswa Kelas VII-A SMPN 3 Masbagik Tahun Pelajaran 2020/2021 - Yani, A. Sar’i (MASALIQ, 2021)
This study aims to find out that the use of the Reciprocal Teaching method can improve students' reading comprehension skills in grade VII-A during the COVID-19 period at SMPN 3 Masbagik, Wanasaba district, East Lombok district. The research was carried out for 3 months starting from October to December 2020. The form of this research was classroom action research. From the results of the first cycle, it can be seen that the students' reading comprehension ability averaged 63.5 while in the second cycle there was an increase to 77.73. This situation shows that the improvement of students' reading comprehension learning using the Reciprocal Teaching method can be said to be successful, although individual mastery has not been fully achieved but class mastery has increased from 67% in the first cycle to 90% in the second cycle.